The role of STAT3 in the colorectal cancer therapy (Journal of Medical Science, 2020)
Colorectal cancer is a malignant tumour of the digestive system, more common in the elderly than in younger individuals. The incidence rate in the United States and the European Union is increasing by an average of 4.2% to 4.6% annually. There is emerging evidence that deregulation of the signalling pathway and abnormal expression and activation of genes is the main reason for the development of colorectal cancer. Signal transducer and activator of transcription (STAT3) is a transcription factor of signal transduction and transcriptional activation of target genes which plays important roles in proliferation, differentiation, apoptosis and other physiological processes. It has been confirmed that abnormal activation of STAT3 is involved in the development of tumours, so the identification of STAT3 inhibitors is a promising strategy for cancer chemoprevention and treatment of colorectal cancer. In this review, the roles of STAT3 in the pathogenesis and treatment of colorectal cancer are discussed.